1980
DOI: 10.1037/0022-0167.27.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Holland (1973) model of vocational development with Spanish-speaking clients.

Abstract: A review of the literature revealed that few studies had examined whether vocational development theories and interest inventories researched primarily with white samples are meaningful for Spanish-speaking individuals. This study found that the six Holland personality types as measured by the Harrington/O'Shea System for Career Decision-Making (CDM) were present in four different Hispanic subcultures: Chicano, Puerto Rican, Cuban, and South American. The types were ordered according to the Holland hexagonal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…However, it is yet unclear about how that might be done. Although older studies insisted that most inventories are valid for minorities (Harrington & O'Shea, 1980;Kimball, Sedlacek, & Brooks, 1973;Lamb, 1976), more recent studies have demonstrated the lack of fit and inconsistencies in the career interest structures for minorities (Carter & Swanson, 1990;Koegel et al, 1995).…”
Section: Use Of Career Instrumentsmentioning
confidence: 99%
“…However, it is yet unclear about how that might be done. Although older studies insisted that most inventories are valid for minorities (Harrington & O'Shea, 1980;Kimball, Sedlacek, & Brooks, 1973;Lamb, 1976), more recent studies have demonstrated the lack of fit and inconsistencies in the career interest structures for minorities (Carter & Swanson, 1990;Koegel et al, 1995).…”
Section: Use Of Career Instrumentsmentioning
confidence: 99%
“…Many tests have validated translations. For example, the Strong Interest Inventory has a validated Spanish translation (Hansen & Fouad, 19841, as does the Career Decision-Making System (Harrington & O'Shea, 1980). Valid translations usually require a three-or four-step process.…”
Section: Translationmentioning
confidence: 99%
“…Tomlinson and Evans-Hughes (1991) and Montoya and DeBlassie (1985) investigated patterns of interests among whites and Latinos/Hispanics and found no significant differences between the groups in scale scores. Harrington and O'Shea (1980) found that the Spanish version of the CDM was valid and very similar to Holland's (1985c) Vocational Preference Inventory given to whites. Similarity of scale scores in the U.S. and Mexico may be generalized to Latinos/Hispanics within the U.S. Fouad and her colleagues investigated whether vocational interests are more similar across cultures in areas based on natural and universal laws (e.g., math and science), than those interests based on human laws (e.g., teaching, management) (Fouad, Hansen, & Arias-Galicia, 1986Fouad & Hansen, 1987).…”
Section: Interventionmentioning
confidence: 75%
“…Counselors may want to check with test publishers for valid Spanish translations, and consult test manuals, which should provide users with a description of the complete translation process. Another instrument that has undergone a rigorous process of linguistic equivalence is the Career DecisionMaking System (CDM; Harrington & O'Shea, 1980).…”
Section: Language and Linguistic Equivalencementioning
confidence: 99%